Regional economic losses from excluding Roma women from labour market in Serbia - Tanaskovic, Svetozar; Jandrić, Maja; Molnar, Dejan (Industrija, 2023)
In this paper, we calculate the economic costs of labour market exclusion of Roma women at the NUTS 2 level in Serbia in terms of output and fiscal benefits. The approach relies on the analysis of a scenario in which there are no differences in the level of wages or in labour force participation and employment rates between Roma and non-Roma labour market participants. We use Labour Force Survey (LFS) data from 2019 as a basis for the comparison of the Roma and non-Roma populations in terms of expected gross earnings for working-age individuals provided they are employed. The results show that the total economic loss (output + fiscal) due to the exclusion of Roma women from the labour market in Serbia amounts to about 197.7 million euros on an annual basis. Of that, 70.5% (139.3 million euros) come from output/productivity losses, and 29.5% (58.4 million euros) from fiscal losses. The largest contribution to total economic losses comes from the South and Eastern Serbia region (37.25%), followed by the Vojvodina region (28.25%), the Belgrade region (24.03%) and the Šumadija and Western Serbia region (10.46%).
Keywords: Roma women, labour market, economic loss, Serbia, NUTS 2 regions.